2020
DOI: 10.1515/jbnst-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Sample Size Calculation in Economic Experiments

Abstract: Clinical studies and economic experiments are often conducted with randomized controlled trials. In clinical studies, power calculations are carried out as a standard. But what’s about economic experiments? After describing the basic idea of the calculation procedure in a brief tutorial, I tackle the practice of sample size calculations in the field of experimental economics by considering the publications of 5 economic journals in the period 2000–2018. These are two top-ranked economic journals (Quarterly Jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…After excluding students who were either postgraduate students, part-time students, or non-local students, 44 and 37 students were enrolled in the intervention and control groups, respectively. As the calculation of the required sample size depends on the outcome variable of this study (students’ views on regional cooperation) ( Dong and Maynard, 2013 ; Gruener, 2020 ), and the outcome variable has not been quantified before, we have to rely on expert estimates to determine the required sample size. It is suggested that a sample of 10–20 can yield relatively high statistical power to detect moderate differences between groups for experimental research in the literature ( Roscoe, 1975 ; Sekaran and Bougie, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…After excluding students who were either postgraduate students, part-time students, or non-local students, 44 and 37 students were enrolled in the intervention and control groups, respectively. As the calculation of the required sample size depends on the outcome variable of this study (students’ views on regional cooperation) ( Dong and Maynard, 2013 ; Gruener, 2020 ), and the outcome variable has not been quantified before, we have to rely on expert estimates to determine the required sample size. It is suggested that a sample of 10–20 can yield relatively high statistical power to detect moderate differences between groups for experimental research in the literature ( Roscoe, 1975 ; Sekaran and Bougie, 2016 ).…”
Section: Methodsmentioning
confidence: 99%